PERANAN KARANG TARUNA DALAM MEMBINA KENAKALAN REMAJA DI DESA BAGELEN KABUPATEN PESAWARAN - Angga Yudana Saputra; Hermi Yanzi; Yunisca Nurmalisa (Jurnal Kultur Demokrasi, 2015)
This research aimed to explain the role of social youth groups bagelen putra in tackling misbehavior teenagers in the village of Bagelen Gedong Tataan sub-district Pesawaran regency year 2014. Method of this research was using descriptive method with sample of 25 respondents. Basic technique of data collection was using questionnare and data analysis descriptive analysis. Based on the result of the research on 25 respondents, it obtained the data in the indicator of become agent of change was 44%, group facilitator was 52%, as the organizers was 48% and indicators convey information was 48%. As well as on the variables of teenagers misbehavior, data obtained on indicator of drug use was 48%, indicators of destructing public facilities was 44%, indicators of sexual harassment was 60%, indicators of high speed on the street was 44%, and indicators of brawl was 48%.Penelitian ini bertujuan untuk menjelaskan peranan karang taruna Bagelen Putra dalam menanggulangi masyarakat terhadap kenakalan remaja di Desa Bagelen Kecamatan Gedong Tataan Kabupaten Pesawaran Tahun 2014. Metode penelitian ini menggunakan metode deskriptif dengan sampel 25 responden. Teknik pokok pengumpulan data menggunakan angket dan analisis data menggunakan analisis deskriptif. Berdasarkan hasil penelitian terhadap 25 responden diperoleh data pada indikator menjadi agen perubahan 44%, indikator sebagai memfasilitasi kelompok 52%, sebagai pengorganisir 48% dan indikator menyampaikan informasi 48%. Serta pada variabel kenakalan remaja diperoleh data pada indikator penggunaan narkoba 48%, indikator merusak fasilitas umum 44% , indikator pelecehan seksual 60% indikator kebut-kebutan dijalan 44%, dan indikator tawuran 48%.Kata kunci:membina remaja, kenakalan remaja, peranan karang taruna